Perception of socio-affective learning and its contribution to participation in the UdeC Talents enrichment program - Sánchez Ríos, José; Ortiz Lebrón , Ana Maritza; Betancourt, Gladys (Revista Saberes Educativos, 2024)
The objective of this research was to determine the level of importance that teachers attach to research and creative work in the teaching and learning process of students. Using a Likert scale, with one being low importance and five being very important, all participants placed high importance on research and creative work (four or more points). The inferential analysis focused on academic rank of the professors, academic program in which the professors teach, years of experience teaching, and level of importance. The results showed that there were no significant differences in research, but there were significant differences in two criteria related to creative work.